Practices of looking, transformations in cheering: alliances and rivalries in upper xinguan wrestiling - Costa, Carlos Eduardo (Anuário Antropológico, 2021)
Kindene wrestling is one of the most frequently recorded practices in the Upper Xingu, from the pioneering expeditions of the 19th century to researchers who worked toward the demarcation of the Indigenous Land in the mid-20th century. Even with the recent demographic increase of peoples and the diversification of ethnographic themes addressed, the kindene remains the subject of succinct, if acute, descriptions. Despite this epiphenomenal character, in the midst all the ritual sumptuousness in which it is primarily disputed wrestling mobilizes political strife involving the chieftaincy; historical rivalries that span generations; transformations that consolidate regional systems; emotions and performances between wrestlers and fans. The dynamics of ritual organization, especially of the egitsü, a post-funeral ceremony in honour of chiefs, shuffles inter-ethnic relations. Such configurations promote alliances and oppositions that affect the formation of teams, and, consequently, rearranges the fans at each event. This article gives greater visibility to the relations between playing and cheering, mediated by the faculty of looking, in the celebrations of victories, indicating the transformations unleashed in the relational universe of the peoples of the region. Fundamental positions for ritual combats, the nginiko ("onlookers"), bring to light new angles to deal with the complexity of relationships in the context of the so-called pax xinguana.